2021
DOI: 10.1177/21582440211061565
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Role of Organic Labeling Awareness and Food Safety Attitudes in the Correlation Between Green Product Awareness and Purchase Intentions

Abstract: Improving consumer trust is critical for enhancing purchase intentions. This study assessed the effect of organic labeling awareness and food safety attitudes as mediating variables on the relation between green product awareness and organic food purchase intentions among consumers. The research sample comprised 404 respondents from Shantou, Shenzhen, and Guangzhou, China, collected by systematic random sampling. Structural equation modeling was used to analyze research data. First, green product awareness did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…In columns (3) and (4) of Table 4, we find that female consumers have the stronger preferences for online channel relative to male consumers. Moreover, the coefficient of city demonstrates that female consumers in Guangzhou prefer to purchase branded OIM via online channel, which by W. M. Wong and Tzeng (2021) explained as the impact of consumers’ organic label awareness and food safety awareness in Guangzhou.…”
Section: The Analysis Of Regression Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In columns (3) and (4) of Table 4, we find that female consumers have the stronger preferences for online channel relative to male consumers. Moreover, the coefficient of city demonstrates that female consumers in Guangzhou prefer to purchase branded OIM via online channel, which by W. M. Wong and Tzeng (2021) explained as the impact of consumers’ organic label awareness and food safety awareness in Guangzhou.…”
Section: The Analysis Of Regression Resultsmentioning
confidence: 99%
“…In columns (3) and (4) of Table 4, we find that female consumers have the stronger preferences for online channel relative to male consumers. Moreover, the coefficient of city demonstrates that female consumers in Guangzhou prefer to purchase branded OIM via online channel, which by W. M. Wong and Tzeng (2021) explained as the impact of consumers' organic label awareness and food safety awareness in Guangzhou. From the perspective of the market choice propensity of online platform and online channel stickiness, the corresponding coefficient indicates the preference for Taobao platform and positive relationship between the market choice propensity of online platform and online channel stickiness.…”
Section: The Mechanism Analysis Of Online Channel Stickinessmentioning
confidence: 99%
“…Ansu-Mensah's (2021) findings indicated that familiarity with environmentally friendly products influenced consumers' intentions to purchase, driven by factors like pricing, perceived value, and superior quality. When consumers are knowledgeable about green products, they tend to develop an awareness that translates into intentions to purchase, as highlighted by (Wong & Tzeng, 2021).…”
Section: Awareness Of Green Productsmentioning
confidence: 99%
“…Raising awareness of consumers about certificate inquiry will be beneficial in increasing the demand for organic products. According to the research of de Magistris and Gracia (2012), Grashuis (2021), and Wong and Tzeng (2021), the use of organic logos on products increases consumers' awareness of organic products.…”
Section: Consumers' Perceptions Of Organic Milk and Dairy Productsmentioning
confidence: 99%